2021
DOI: 10.4081/mrm.2021.766
|View full text |Cite
|
Sign up to set email alerts
|

A single-center comparative study of lung ultrasound <em>versus</em> chest computed tomography during the COVID-19 era

Abstract: Background: Lung ultrasound (LUS) is a bedside imaging tool that has proven useful in identifying and assessing the severity of pulmonary pathology. The aim of this study was to determine LUS patterns, their clinical significance, and how they compare to CT findings in hospitalized patients with coronavirus infection.Methods: This observational study included 62 patients (33 men, age 59.3±15.9 years), hospitalized with pneumonia due to COVID-19, who underwent chest CT and bedside LUS on the day of admission. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies showed that in COVID-19 pneumonia still at an early stage, LUS can detect early lung lesions even when CT scan is almost normal. Furthermore, there was a relationship between the abnormalities detected by the LUS and CT, especially between the presence of more than 2 B-lines on LUS and ground glass opacity areas on CT and between subpleural consolidations on LUS and consolidation areas on CT [ 36 , 37 , 38 , 50 ]. Recently, Lupia et al enrolled 208 patients with COVID-19 respiratory symptoms who underwent nasal swab and LUS according to a scanning protocol [ 47 ].…”
Section: The Pathophysiology Of Severe Pneumonia/ards Due To Covid-19...mentioning
confidence: 99%
“…Several studies showed that in COVID-19 pneumonia still at an early stage, LUS can detect early lung lesions even when CT scan is almost normal. Furthermore, there was a relationship between the abnormalities detected by the LUS and CT, especially between the presence of more than 2 B-lines on LUS and ground glass opacity areas on CT and between subpleural consolidations on LUS and consolidation areas on CT [ 36 , 37 , 38 , 50 ]. Recently, Lupia et al enrolled 208 patients with COVID-19 respiratory symptoms who underwent nasal swab and LUS according to a scanning protocol [ 47 ].…”
Section: The Pathophysiology Of Severe Pneumonia/ards Due To Covid-19...mentioning
confidence: 99%